Penegakan Hukum Tindak Pidana Penipuan Berbasis Online dengan Modus Giveaway di Platform Media Sosial: Studi kasus Polres Tanjungbalai - Linawati, Linawati; Andryan, Andryan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The advancement of information technology that is increasingly developing in Indonesian society allows them to access the information they want more easily. The progress of information technology can also influence people to do things that are not good, which can lead to the emergence of new online-based criminal acts. Giveaway can be interpreted as an activity carried out by someone by giving prizes that can be money or goods with various specific conditions that must be met. The application of the article according to the Criminal Code (KUHP) contained in article 378. And regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) which is contained in article 45 A. The type of research used is qualitative research, which is a research method aimed at explaining and analyzing phenomena, studies, social activities, attitudes, beliefs, perceptions, and thoughts of individuals and groups.